2021
DOI: 10.3390/agronomy11081448
|View full text |Cite
|
Sign up to set email alerts
|

Water Table Fluctuation and Methane Emission in Pineapples (Ananas comosus (L.) Merr.) Cultivated on a Tropical Peatland

Abstract: Inappropriate drainage and agricultural development on tropical peatland may lead to an increase in methane (CH4) emission, thus expediting the rate of global warming and climate change. It was hypothesized that water table fluctuation affects CH4 emission in pineapple cultivation on tropical peat soils. The objectives of this study were to: (i) quantify CH4 emission from a tropical peat soil cultivated with pineapple and (ii) determine the effects of water table depth on CH4 emission from a peat soil under si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Although some incubation experiments have found that under anaerobic conditions, soil temperature has a significant and strong positive exponential effect on soil peat CH 4 emissions (Sjögersten et al, 2018 ), no clear effect of soil temperature on CH 4 emissions has been reported under field experiments on tropical peatlands, probably due to the small variation of temperature in the tropics (Deshmukh et al, 2020 ; Jauhiainen et al, 2014 ; Luta et al, 2021 ). Similarly, we did not find a predictive relationship between in situ temperature and CH 4 emissions.…”
Section: Discussionmentioning
confidence: 99%
“…Although some incubation experiments have found that under anaerobic conditions, soil temperature has a significant and strong positive exponential effect on soil peat CH 4 emissions (Sjögersten et al, 2018 ), no clear effect of soil temperature on CH 4 emissions has been reported under field experiments on tropical peatlands, probably due to the small variation of temperature in the tropics (Deshmukh et al, 2020 ; Jauhiainen et al, 2014 ; Luta et al, 2021 ). Similarly, we did not find a predictive relationship between in situ temperature and CH 4 emissions.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Indonesian tropical peatlands showed that changes in land use from the swamp and drained forest to cassava or coconut cultivation areas result in a lower water table and lead to decreasing CH4 emission, while the change to lowland paddy results in increasing the water table which eventually leads to increasing CH4 emission (Inubushi et al 2005). Luta et al (2021) found that CH4 emission from lysimeters under simulated low-and highwater table fluctuation of tropical peatland is controlled by water-table. Wong et al (2020) reported a positive exponential relationship between CH4 emission and groundwater level, and rewetting tropical peatlands results in increasing CH4 emissions (Kumar et al 2020).…”
Section: Relationship Between Peat Characteristics and Ch4 And Co2 Em...mentioning
confidence: 99%